Simultaneous effects of legume cultivation on carbon and nitrogen accumulation in soil - Virk, Ahmad Latif; Lin, Bai-Jian; Kan, Zheng-Rong; Qi, Jian-Ying; Dang, Yash Pal; Lal, Rattan; Zhao, Xin; Zhang, Hai-Lin (Advances in agronomy, 2022)
The carbon (C) and nitrogen (N) cycles play an important role in agro-ecosystems. The interaction of both elements is a complex process, i.e., high soil organic carbon (SOC) and low N levels affect soil microbial biology and nutrient balance which can be improved through input of N. Therefore, an increase in N favors SOC sequestration by improving microbial activities. Legume-based biological nitrogen fixation (BNF) contributes about 50–70TgNha−1 globally, and strongly impacts SOC sequestration. However, research information about the process of SOC sequestration with an increase in N by legume cultivation is scant. This review highlights the principal mechanisms by which cultivation of legume can enhance soil fertility and functioning through interaction of N and SOC, and vice versa. Legume cultivation leads to a simultaneous increase in N and SOC through rhizodeposition and root senescence and decomposition. Legume cultivation can also improve SOC due to the increased microbial activity and subsequent soil structural improvement (aggregation) induced by the addition of organic residues with favorable C/N ratio. Legume inclusion significantly increased SOC sequestration potential than other cropping systems, and legume residue addition has higher decomposition rate than cereals that increase SOC addition rate. However, additional research is needed to understand the pertinent role of root exudates and associated microbes in sequestration of SOC and N. Synthesis of the available information indicates that legume cultivation is an important option to sequester SOC and N for sustainable food production and environmental restoration.